Exercise as a Potential Treatment for Drug Abuse: Evidence from Preclinical Studies - Smith, Mark A.; Lynch, Wendy J. (Frontiers in Psychiatry, 2012)
Epidemiological studies reveal that individuals who engage in regular aerobic exercise are less likely to use and abuse illicit drugs. Until recently, very few studies had examined the causal influences that mediate this relationship, and it was not clear whether exercise was effective at reducing substance use and abuse. In the past few years, several preclinical studies have revealed that exercise reduces drug self-administration in laboratory animals. These studies have revealed that exercise produces protective effects in procedures designed to model different transitional phases that occur during the development of, and recover from, a substance use disorder (e.g., acquisition, maintenance, escalation, and relapse/reinstatement of drug use). Moreover, recent studies have revealed several behavioral and neurobiological consequences of exercise that may be responsible for its protective effects in these assays. Collectively, these studies have provided convincing evidence to support the development of exercise-based interventions to reduce compulsive patterns of drug intake in clinical and at-risk populations.